2022
DOI: 10.3390/children9111728
|View full text |Cite
|
Sign up to set email alerts
|

Overweight Prevalence among Rural Adolescents by Household Head Obesity and Socio-Economic Status in Limpopo, South Africa

Abstract: Background: Childhood obesity has become the most important and growing public health problem in the world. They add to public health challenges by increasing the burden of chronic non-communicable diseases. However, in spite of its importance, there is limited literature that evaluates the prevalence of obesity among rural adolescents in sub-Saharan Africa. We report the first study to present an insight into rural black overweight South African children and the physical characteristics and socio-economic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…20 However, a 2022 study in South Africa reported no significant association between childhood obesity and household SES. 21 More girls were found to be overweight compared to boys, and similar findings have been reported earlier. 22,23 Finally, the relationship between age and BMI showed significant association, and similar results have been reported by studies done in Iraq and Kuwait.…”
Section: Discussionsupporting
confidence: 88%
“…20 However, a 2022 study in South Africa reported no significant association between childhood obesity and household SES. 21 More girls were found to be overweight compared to boys, and similar findings have been reported earlier. 22,23 Finally, the relationship between age and BMI showed significant association, and similar results have been reported by studies done in Iraq and Kuwait.…”
Section: Discussionsupporting
confidence: 88%